2020
DOI: 10.3390/foods9020163
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Functional and Structural Properties of Pasta Enriched with a Debranning Fraction from Purple Wheat

Abstract: A colored and fiber-rich fraction from the debranning of purple wheat was incorporated at 25% into semolina-and flour-based pasta produced on a pilot-plant scale, with the aim of increasing anthocyanin and total phenolic content with respect to pasta obtained from whole pigmented grains. The debranning fraction impaired the formation of disulfide-stabilized protein networks in semolina-based systems. Recovery of phenolics was impaired by the pasta making process, and cooking decreased the phenolic content in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, high ratios (15-20%) of these ingredients had a negative effect on the sensory and cooking quality of pasta. In another study [41], the authors added a debranning bran fraction from purple wheat into semolina. They observed that the level of anthocyanins and phenolics significantly increased following pasta enrichment.…”
Section: Enrichment Of Wheat Pasta With Grains and Seedsmentioning
confidence: 99%
“…However, high ratios (15-20%) of these ingredients had a negative effect on the sensory and cooking quality of pasta. In another study [41], the authors added a debranning bran fraction from purple wheat into semolina. They observed that the level of anthocyanins and phenolics significantly increased following pasta enrichment.…”
Section: Enrichment Of Wheat Pasta With Grains and Seedsmentioning
confidence: 99%
“…The technology also enables to isolate aleurone-rich fractions, which can be used as functional ingredients [86]. Abbasi et al have recently formulated pasta enriched with a debranning fraction from purple wheat [51]. The debranning fraction (25%) was added to flour and to semolina by dry mixing, and macaroni pasta samples were prepared.…”
Section: Raw Materials Processing Pasta-making and Pasta Cookingmentioning
confidence: 99%
“…Our results showed a firmness loss in powder‐enriched Rubus paste, while the resilience did not differ significantly. This could find an explanation by adding gluten‐free flour, which dilutes the gluten network and makes it weaker, as confirmed by other authors in pasta samples with non‐gluten flour enriched (Albors et al ., 2016; Parizad et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%